2020
DOI: 10.3389/fphys.2020.00221
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Serotonin in the Influence of Intense Locomotion on the Behavior Under Uncertainty in the Mollusk Lymnaea stagnalis

Abstract: The role of serotonin in the immediate and delayed influence of physical exercise on brain functions has been intensively studied in mammals. Recently, immediate effects of intense locomotion on the decision-making under uncertainty were reported in the Great Pond snail, Lymnaea stagnalis (Korshunova et al., 2016). In this animal, serotonergic neurons control locomotion, and serotonin modulates many processes underlying behavior, including cognitive ones (memory and learning). Whether serotonin mediates the be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 55 publications
2
24
0
Order By: Relevance
“…Similar effects have also been observed in other freshwater and marine gastropod species, such as Leptoxis carinata, Stagnicola elodes, Tegula fasciatus, Urospalpinx cinerea, Nucella ostrina, and Lithopoma americanum after exposure to either venlafaxine, citalopram, or other antidepressants [31,32,93]. In gastropod species, it is well-known that locomotion and mucus secretion are strongly serotonin-dependent [94][95][96][97]. As venlafaxine acts as a serotonin re-uptake inhibitor and, thus, interferes with the serotonin metabolism, this interaction may disturb the co-ordination of mucus secretion, ciliate epithelium activity, and muscle cell functions [96].…”
Section: Discussionsupporting
confidence: 71%
“…Similar effects have also been observed in other freshwater and marine gastropod species, such as Leptoxis carinata, Stagnicola elodes, Tegula fasciatus, Urospalpinx cinerea, Nucella ostrina, and Lithopoma americanum after exposure to either venlafaxine, citalopram, or other antidepressants [31,32,93]. In gastropod species, it is well-known that locomotion and mucus secretion are strongly serotonin-dependent [94][95][96][97]. As venlafaxine acts as a serotonin re-uptake inhibitor and, thus, interferes with the serotonin metabolism, this interaction may disturb the co-ordination of mucus secretion, ciliate epithelium activity, and muscle cell functions [96].…”
Section: Discussionsupporting
confidence: 71%
“…Indeed, stimulating effects of running on the brain function in humans and rodents have been repeatedly demonstrated [22][23][24] . Decreased anxiety 25,26 , augmented neurogenesis 22,27,28 , improved memory and learning 22,27 , facilitation of decision-making 20,21,29 reported in numerous studies would be important or even crucial for surviving in the novel conditions. Recent studies reported behavioral benefits of intense locomotion for subsequent orientation in a novel environment in an evolutionarily distant animal, the mollusc Lymnaea stagnalis 20,21 , suggesting that this phenomenon might have deep roots in evolution.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that feedforward activation of physical and cognitive abilities following intense locomotion can be beneficial and even critical for survival in the novel environment. In other words, intense locomotion can be used as a predictor of novelty and activate mechanisms of biological and cognitive "preadaptation" to less familiar environments 20,21 . Indeed, stimulating effects of running on the brain function in humans and rodents have been repeatedly demonstrated [22][23][24] .…”
Section: Discussionmentioning
confidence: 99%
“…Insulin spike is evoked as an anticipation of food. Snails have been fed daily before CTA training, we may think that this rhythm was learned by snails (Aonuma et al, 2020). Thus, they expected to get fed, and insulin is released in advance, prior to the food and to an increase in the glucose concentration.…”
Section: Discussionmentioning
confidence: 99%